Mark as story : an introduction to the narrative of a gospel - Rhoads, David M. (Fortress Press, 2012)
"For thirty years, Mark as Story has introduced readers to the rhetorical and narrative skill that makes Mark so arresting and compelling a story. Rhoads, Dewey, and Michie have helped to pioneer our appreciation of the Gospels, and Mark in particular, as narratives originally created in an oral culture for oral performance. New in this edition are a revised preface and an afterword describing the significant role Mark as Story has played in the development of narrative criticism"--Publisher description